Improving Students Science Process and Critical Thinking Skills Using Semi-Research Patterns Practicum - Jahro, Iis Siti; Darmana, Ayi; Sutiani, Ani (JTK (Jurnal Tadris Kimiya), 2021)
The old pattern of practicum implementation has less impact on increasing studentsâ€™ science process skills and critical thinking. Therefore, implementing practicum with a semi-research pattern has been carried out by involving the lecturer and laboratory assistant. The subjects of this research were 40 students in Universitas Negeri Medan. The method is classroom action research consisting of two cycles. Each cycle includes planning, action, reflection, and evaluation. Instrumentâ€™s research is the observation sheet and essay test. The results of descriptive data analysis show that implementing practicum with a semi-research pattern can improve studentsâ€™ science process critical thinking skills, especially in planning experiments by 88.3% and critical thinking skills in evaluating by 82.3%. Â